Lessons to be learnt from Harizal's case - Abd Razak, Dzulkifli (2005)
THE overwhelming outpouring of sympathy for Ahmad Harizal Ahmad Fauzie, the socalled National Service dodger, shows that Malaysian society is very much alive and alert. It is a sobering feeling that they care when it matters. This is, of course, not to say that Malaysians are disrespectful of the court of law. The law must be obeyed and, as the saying goes, justice must not only be done but seen to be done as well. But justice can come in many forms; some say it is a matter of interpretation. Re calling a narration from the early days of Islam, one could argue that there are different styles of administering justice. In this case, it was a story of a boy who stole something to eat. Brought before the authorities to he punished, the boy was instead set free, recognised as a victim of an inequitable and unjust society. In a way, what the boy did was a reflection of the level of social justice of the day. The boy was too poor to feed himself, and he had to resort to "stealing" to stay alive.